2023
DOI: 10.1101/2023.11.11.23298408
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating the Impact of Diagnostic Stewardship in Community-Acquired Pneumonia with Syndromic Molecular Testing: A Randomized Clinical Trial

Dagfinn L. Markussen,
Sondre Serigstad,
Christian Ritz
et al.

Abstract: ImportanceLower respiratory tract infections, including community-acquired pneumonia (CAP), are a leading cause of hospital admissions and mortality. An aetiological diagnosis of CAP is delayed due to long turnaround times with laboratory testing. Rapid microbiologic diagnosis is imperative for the management of CAP and may limit antibiotic overuse. Molecular tests have the potential to optimize treatment decisions and management of CAP, but limited evidence exists to support their routine use.ObjectiveTo dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
(26 reference statements)
1
2
1
Order By: Relevance
“…Two recent randomised trials have explored the efficacy of multiplex real-time PCR in non-invasive respiratory samples to reduce antibiotic use in CAP, yielding divergent results. 12,13 Our main finding aligns with a trial conducted across three Danish medical emergency departments, wherein the integration of point-of-care PCR into the diagnostic regimen did not increase the number of CAP patients with a more targeted and appropriate use of antibiotics. 12 Conversely, a single-centre randomised trial in Norway revealed that implementing a PCR-based panel for rapid testing in the emergency department facilitated swifter and more tailored antibiotic therapy for individuals with suspected CAP.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Two recent randomised trials have explored the efficacy of multiplex real-time PCR in non-invasive respiratory samples to reduce antibiotic use in CAP, yielding divergent results. 12,13 Our main finding aligns with a trial conducted across three Danish medical emergency departments, wherein the integration of point-of-care PCR into the diagnostic regimen did not increase the number of CAP patients with a more targeted and appropriate use of antibiotics. 12 Conversely, a single-centre randomised trial in Norway revealed that implementing a PCR-based panel for rapid testing in the emergency department facilitated swifter and more tailored antibiotic therapy for individuals with suspected CAP.…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, this difference was not correlated with significant variations in lenght of hospital stay, mortality rates, and hospital readmissions. 13 In our trial, although the multiplex real-time PCR plus conventional microbiological testing group achieved an aetiological diagnosis more frequently and more rapidly than the control group, this did not correlate with a significant reduction in antibiotic consumption. Among the factors that may have contributed to this finding is physician behaviour.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations